2003
DOI: 10.1103/physreve.68.026215
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of noisy repellors

Abstract: We study the effects of additive noise on the lifetimes of chaotic repellors. Using first order perturbation theory we argue that noise will increase the lifetime if the escape holes lie in regions where the unperturbed density is higher than in the immediate vicinity and that it decreases if the density is lower. Numerical experiments support the qualitative conclusions also beyond perturbation theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Using (15) and (16) we explicitly show that the decay rate of the first return time distribution of a set E in a closed system, given by the leading pole of F (z), is equal to the escape rate of the system open on E (given by the leading zero of ζ −1 op (z)), a previously heuristically derived result [1]. Furthermore, from Kac's lemma F ′ (1) = 1/µ B and thus, using (15) in (16) we have…”
Section: Small Hole Asymptoticsmentioning
confidence: 79%
See 1 more Smart Citation
“…Using (15) and (16) we explicitly show that the decay rate of the first return time distribution of a set E in a closed system, given by the leading pole of F (z), is equal to the escape rate of the system open on E (given by the leading zero of ζ −1 op (z)), a previously heuristically derived result [1]. Furthermore, from Kac's lemma F ′ (1) = 1/µ B and thus, using (15) in (16) we have…”
Section: Small Hole Asymptoticsmentioning
confidence: 79%
“…On the contrary, in [9] it was observed that varying the position of the hole has a strong effect on the average lifetime of chaotic transients due to the complex periodic orbit structure in chaotic maps. This dependence on the position of the hole has generated a renovated interest among both physicists and mathematicians; in [10] the escape rate was shown to have non-trivial dependence on the position and non-monotonic dependence on the size of the holes, general results on the asymptotic behavior for small holes have been studied in [11,12,13,14] whilst in [15,16], the addition of noise is investigated. Open problems and reviews of this material can be found in [17,8,1].…”
Section: Introductionmentioning
confidence: 99%
“…An important task for the future will be to catalog and classify the many possible forms of interaction between nonlinearity and stochasticity, including noise‐induced chaos. For now, the list is still growing – we note in particular recent analyses of how noise can extend the lifetime of chaotic transients (Faisst and Eckhardt 2003) and of how chaotic saddles facilitate noise‐driven jumps between attractors (Kraut and Feudel 2002, 2003) – and ecologists are still largely unaware of it.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs in empirically grounded models for host–pathogen (Rand and Wilson 1991, Billings and Schwartz 2002) and predator–prey dynamics (below). Moreover, noise can actually increase the typical length of time that trajectories remain near a chaotic repeller (Faisst and Eckhardt 2003). Chaotic repellers often become chaotic attractors at nearby parameter values, which is true in our case (Fig.…”
Section: What Is Noise‐induced Chaos?mentioning
confidence: 99%
“…Transient behaviour can be relatively persistent and can remain even after far exceeding the bifurcation value k c [55]. In addition the steady state can be sensitive to any perturbations which could cause the system to re-enter a potentially long chaotic transient again [56]. The behaviour of the two species system for k 11 ≥ k c seems to exhibit such chaotic transient behaviour with a quasi-periodic steady state (FIG.…”
Section: Dimensionality and Chaosmentioning
confidence: 99%